Teknologi Pendidikan sebagai Arena Etika: Mediasi Nilai oleh Mahasiswa dalam Perspektif Kritis Andrew Feenberg : Penelitian - Nida Hanifa; Adinuringtyas Herfi Rahmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article explores the role of students in mediating values through the use of educational technology, employing a qualitative approach grounded in a literature-based study of the critical philosophy of technology developed by Andrew Feenberg. The focus of this study is on students' activities in creating digital media such as instructional videos that reflect ethical dimensions within digital learning spaces. Data were obtained through a literature review of both primary and secondary sources, including the works of Feenberg, Bayne, Selwyn, and Nkomo et al. The analysis reveals that students have the potential to act as agents of value construction through the process of democratic rationalization, in which educational technology initially neutral and technical acquires new meaning through its practical use. The study identifies a gap in educational technology research, which tends to emphasize effectiveness over ethical considerations. These findings underscore the importance of viewing educational technology not merely as a technical instrument but as an ethical space that shapes the relationship between users and values. This article offers a conceptual contribution to the field of educational technology by positioning students as reflective subjects within the ethical configuration of technology.